Do nonprofit leaders challenge political leaders? - Oto Potluka; Lenka Svecova; Lucie Zarubova (University of Basel, Center for Philanthropy Studies (CEPS), 2020)
Successful place-based leadership is based on functional networks, dialogue among stakeholders, political support and funding, and sharing power. The EU-funded Integrated Urban Development Plans (IUDPs) require the participation of citizens and local nonprofit organizations. When creating an opportunity for informal leadership, it is not clear whether the informal leadership fills the position of formal political leadership. On the data from the implementation of several IUDPs in the Czech Republic, we tested whether formal leadership becomes dispersed and informal place leadership fills the vacuum instead. Our research did not find differences in the change of civic political engagement at the local level related to the success and failure of the IUDPs strategies. Local civic engagement and nonprofit leadership are challenging formal local political leadership. Nevertheless, their success is limited as there is also missing dialogue among the local movements and nonprofit leaders when finding solutions to particular local problems.
Keywords: 330; Local development; Place leadership; Participation; Political competition; Local parties